The value of didactic-pedagogical skills of canoe-polo technical - Vastola, R.; Sgambelluri, R.; Di Tore, S.; Buglione, A.; Prosperi, R.; Cecoro, G.; Carlomagno, N.; Sibilio, M. (Journal of Human Sport & Exercise, 2012)
Canoe-polo is a team sport. It is played in over 50 countries around the world. The role of coach concerns not only the technical - tactics skills but also the managerial, organizational and logistical skills of the players. From the point of view of teaching methodology, the canoe polo coach must be aware of the fact that his role always involves the role of teacher, and to excel in the performance of this function, must possess a number of characteristics that define the area of his specifically pedagogical jurisdiction The aim of the research is to define the elements characterizing the performance model in canoe polo that are the most important in developing a technique, tactics and conditional plan in order to provide the coach the most appropriate knowledge to organize a didactically coherent process to the requires of the group - team. The experimental research was carried out on two subjects of the 2010 Italian champions (CN Posillipo in Naples), during eight matches of the Italian Canoe Polo Championship. The research project provided for the monitoring of the heart rate (HR) during the races by teams polar heart rate monitors system, with a sampling rate of 5s per subject. The acquisitions were subsequently analyzed with a dedicated software Polar Pro Trainer 5.2. The results in this pilot study show, canoe-polo like many other team games where you use a ball, it is an intermittent sport with a high metabolic intensity (4.8).